Development of a Blocking Primer to Inhibit the PCR Amplification of the 18S rDNA Sequences of Litopenaeus vannamei and Its Efficacy in Crassostrea hongkongensis - Liu, Cong; Qi, Ren-Jie; Jiang, Jing-Zhe; Zhang, Ming-Qing; Wang, Jiang-Yong (Frontiers in Microbiology, 2019)
Diversity analyses of the eukaryotic microorganisms in the gut of marine animals is hampered by the presence of host DNA in the samples. PCR amplification of rRNA genes of eukaryotic microorganisms is inefficient with universal primers targeting 18S rRNA gene when the host DNA is dominant. In this study, we designed several blocking primers to inhibit PCR amplification of rRNA genes of the shrimp Litopenaeus vannamei, and tested their efficacy on the oyster Crassostrea hongkongensis. We first compared the intensity of PCR product bands obtained with and without the blocking primers. Then, one primer was selected for further verification using high-throughput sequencing. Our results showed that X-BP2-DPO was the most effective blocking primer in suppressing the host 18S amplification compared to nine other candidates. The inhibition rate was 99% for the amplification of shrimp rDNA, and 17% for the amplification of oyster rDNA. The concentration of the blocking primer in the PCR mixture was an important factor to be considered in the experimental design. The development of blocking primers provided a valid method to study the composition and characteristics of eukaryotic microorganisms in shrimp gut for a better understanding of its diets.